2021
DOI: 10.1101/2021.09.06.459167
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Social belonging: Brain structure and function is linked to membership in sports teams, religious groups and social clubs

Abstract: Human behaviour across the life span is driven by the psychological need to belong, from kindergarten to bingo nights. Being part of social groups constitutes a backbone for communal life, and confers many benefits for physical and mental health. Capitalizing on neuroimaging and behavioural data from ~40.000 participants from the UK Biobank population cohort, we used structural and functional analyses to explore how social participation is reflected in the human brain. Across three different types of social gr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 112 publications
0
1
0
Order By: Relevance
“…A study of the neural signatures of loneliness in this cohort revealed that the default mode network (DMN) is involved in the perception of social isolation: lonely individuals exhibited enhanced functional connectivity in this network and greater integrity of the fornix pathway white matter tract (Spreng et al 2020). A study of social participation as reflected by membership in a social group confirmed that the DMN-including brain regions such as the ventromedial prefrontal cortex, fusiform gyrus, and anterior cingulate cortex along with the limbic network-is important for social belonging (Kieckhaefer et al 2021). It was reported that variations in gray matter volume in brain regions associated with social information processing including the temporoparietal junction, ventromedial prefrontal cortex, and superior temporal sulcus in middle-aged adults were mainly influenced by socio-environmental factors and activities such as household size and daily routines (Kiesow, Uddin, et al 2021).…”
Section: Large-scale Neuroimaging Investigations For Interpersonal An...mentioning
confidence: 98%
“…A study of the neural signatures of loneliness in this cohort revealed that the default mode network (DMN) is involved in the perception of social isolation: lonely individuals exhibited enhanced functional connectivity in this network and greater integrity of the fornix pathway white matter tract (Spreng et al 2020). A study of social participation as reflected by membership in a social group confirmed that the DMN-including brain regions such as the ventromedial prefrontal cortex, fusiform gyrus, and anterior cingulate cortex along with the limbic network-is important for social belonging (Kieckhaefer et al 2021). It was reported that variations in gray matter volume in brain regions associated with social information processing including the temporoparietal junction, ventromedial prefrontal cortex, and superior temporal sulcus in middle-aged adults were mainly influenced by socio-environmental factors and activities such as household size and daily routines (Kiesow, Uddin, et al 2021).…”
Section: Large-scale Neuroimaging Investigations For Interpersonal An...mentioning
confidence: 98%